The Relationship Between Public Sector Employment and Population Health: Evidence From the 1980s and Its Contemporary Implications. (July 2019) - Zhang, Wei; Wu, Qingjun
This article explores the relationship between public sector employment and population health both theoretically and quantitatively. First, we build a theoretical framework to situate public employment in the literature that explores the link between politics and health. We argue that public employment, as an instrument of pro-redistributive policies in both the labor market and the welfare state, improves equality and ultimately health. Second, based on a cross-country dataset from the 1980s, and by applying regression analysis and outlier identification techniques, we find that population health measured by life expectancy improves with the size of public employment. The association is stronger for countries with lower income and for women. When policymakers contemplate downsizing state enterprises and government functions, they should consider the health effect of public employment.